Expanding horizons in the history of science : the comparative approach - Lloyd, G. E. R. (Geoffrey Ernest Richard), 1933- (Cambridge University Press, 2021)
This book challenges the common assumption that the predominant focus of the history of science should be the achievements of Western scientists since the so-called Scientific Revolution. The conceptual frameworks within which the members of earlier societies and of modern indigenous groups worked admittedly pose severe problems for our understanding. But rather than dismiss them on the grounds that they are incommensurable with our own and to that extent unintelligible, we should see them as offering opportunities for us to revise many of our own preconceptions. We should accept that the realities to be accounted for are multi-dimensional and that all such accounts are to some extent value-laden. In the process insights from current anthropology and the study of ancient Greece and China especially are brought to bear to suggest how the remit of the history of science can be expanded to achieve a cross-cultural perspective on the problems.